Research on the Asian Financial Crisis in the late 1990s - Fu, Boyu (Transactions on Economics, Business and Management Research, 2024)
The 1997 Asian financial crisis was a financial storm that began in Thailand and quickly spread to East and Southeast Asia, characterized by currency depreciation, stock market decline, banking system collapse, and economic recession. Thailand, Indonesia, South Korea and other countries have been severely affected. This article conducts research on the above-mentioned crisis and finds that the direct cause of the crisis is Thailand's abandonment of the fixed exchange rate system, leading to the depreciation of the Thai baht. Before the crisis, the economy of Southeast Asian countries grew at a high speed and attracted a large amount of foreign capital. However, after the opening of the capital account, a large amount of short-term capital flowed in, forming a foam economy. The banking system lacks risk management and has accumulated a large number of non-performing loans. The fixed exchange rate system appears fragile under capital outflows. External factors include fluctuations in global capital flows, changes in the monetary policies of developed countries, and instability in international financial markets. The international community, especially the IMF, provided assistance, but the accompanying conditions exacerbated social unrest and economic recession. The lessons learned from the crisis include strengthening financial regulation, avoiding excessive borrowing, establishing sound risk management mechanisms, and enhancing the flexibility of the exchange rate system and the importance of international cooperation.